In the words of the winners the Newbery and Caldecott medals, 2001-2010 - IG Publishing; Association for Library Service to Children; Horn Book, Inc. (Chicago American Library Association, 2011)
Winners of the most respected prizes in children's literature speak out in an exclusive collection of acceptance speeches.
Cover; IN THE WORDS OF THE WINNERS; Copyright; Contents; Preface; The Changing Landscape of Children's Book Publishing; Newbery Medal Books, 2001-2010; Caldecott Medal Books, 2001-2010; 2001; 2002; 2003; 2004; 2005; 2006; 2007; 2008; 2009; 2010; Credits; Index; Backcover.
Electronic reproduction.
Keywords: Newbery Medal -- Bio-bibliography.; Caldecott Medal -- Bio-bibliography.; Children's literature, American -- Bio-bibliography.; Picture books for children -- United States -- Bio-bibliography.; Children -- Books and reading -- United States; Electronic books